Pengaruh Pertumbuhan Aset Dan Struktur Modal Terhadap Profitabilitas Perusahaan Pada Sektor Kesehatan Yang Terdaftar Di BEI - Andine Putri Zulyan (CV. ITTC INDONESIA, 2023)
This research was conducted to determine the effect of asset growth and capital structure on company profitability in the health sector which are listed on the Indonesia Stock Exchange for the quarterly period 2019 – 2021. This research uses quantitative methods with data collection techniques, documentation methods and library research. The population of this study is health sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The results of this study are that there are 4 sample companies taken by researchers, the 4 companies are the result of a decline from 14 companies whose quarterly data are listed on the Indonesian stock exchange. The conclusions in this study are (1) partially, asset growth, which is proxied by asset growth, has a positive and significant effect on profitability, which is proxied by ROE. (2) Partially, the capital structure proxied by DER has a negative and significant effect on profitability, which is proxied by ROE. (3) Simultaneously the asset growth variable which is proxied by asset growth has a positive and significant effect and capital structure which is proxied by DER has a negative and significant effect on profitability which is proxied by ROE.